Analisis Literasi Perpajakan, Sosialisasi Perpajakan, Sanksi Pajak dan Tax Morale Terhadap Kepatuhan Pajak UMKM di Kabupaten Boyolali - Widyaningsih, Dewi; Arta Armilda, Siska; Budi Santoso, Agustinus (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This research aims to partially and simultaneously determine the role of tax literacy, tax socialization, tax sanctions, and tax morale on UMKM tax compliance in Boyolali Regency. Quantitative descriptive methods were used in the research. All UMKM registered with the Boyolali Regency Diskopnaker Office, totaling 48,362 business units, are included in the population of this study. A sample of 100 respondents was collected through random sampling techniques, namely randomly from the population without paying attention to differences in social strata. Data was collected through a questionnaire with a linkert scale to measure respondents answers. Data analysis techniques with multiple linear regression statistical analysis, F test, t test, and determination coefficient. This study proves that tax literacy, tax sanctions, and tax morale partially have a significant positive effect on UMKM tax compliance in Boyolali Regency, while tax socialization has no effect on tax compliance as indicated by insignificant negative results. The variables tax literacy, tax sanctions, tax socialization, and tax morale amounted to 52.4% contributing to tax compliance.